Foreign policy analysis classic and contemporary theory - Hudson, Valerie M. 1958-; Day, Benjamin S. (Lanham, Maryland Rowman & Littlefield, 2020)
"ideal for courses on foreign policy analysis and international relations theory, the third edition offers advanced undergraduates and beginning graduate students a cogently written overview of this broad field of study. Filled with illuminating examples, Hudson and Day consider theory and research at multiple levels of analysis"-- Provided by publisher.
Includes bibliographical references (pages 231-263) and index.
Keywords: International relations -- Decision making; International relations -- Psychological aspects